The Changing Role of Chemotherapy in Locoregionally Advanced Nasopharyngeal Carcinoma: A Updated Systemic Review and Network Meta-Analysis - Liu, Mei; You, Wei; Song, Yi-Bing; Miao, Ji-Dong; Zhong, Xiu-Bo; Cai, Dian-Kun; Xu, Lun; Xie, Lu-Feng; Gao, Yang (Frontiers in Oncology, 2018)
Background/Objective: Both induction chemotherapy (IC) followed by concurrent chemoradiotherapy (CCRT; IC+CCRT) and CCRT plus adjuvant chemotherapy (AC; CCRT+AC) are standard treatments for advanced nasopharyngeal carcinoma (NPC). However, no prospective randomized trials comparing these two approaches have been published yet. We conducted this network meta-analysis to address this clinical question. Method: We recruited randomized clinical trials involving patients with advanced NPC randomly allocated to IC+CCRT, CCRT+AC, CCRT or radiotherapy (RT) alone. Pairwise meta-analysis was first conducted, then network meta-analysis was performed using the frequentist approach. Effect size was expressed as hazard ratio (HR) and 95% confidence interval (CI). Results: Overall, 12 trials involving 3248 patients were recruited for this study, with 555 receiving IC+CCRT, 840 receiving CCRT+AC, 1039 receiving CCRT, and 814 receiving radiotherapy (RT) alone. IC+CCRT achieved significantly better overall survival (hazard ratio [HR], 0.69; 95% confidence interval [CI], 0.51-0.92), distant metastasis-free survival (HR, 0.58; 95% CI, 0.44-0.78) and locoregional recurrence-free survival (HR, 0.67; 95% CI, 0.47-0.98) than CCRT. However, survival outcomes did not significantly differ between IC+CCRT and CCRT+AC, or between CCRT+AC and CCRT arms for all the endpoints. As expected, RT alone is the poorest treatment. In terms of P-score, IC+CCRT ranked best for overall survival (96.1%), distant metastasis-free survival (99.0%) and locoregional recurrence-free survival (87.1%). Conclusions: IC+CCRT may be a better and more promising treatment strategy for advanced NPC; however, head-to-head randomized trials comparing IC-CCRT with CCRT-AC are warranted.